The Effect of Baby Massage on Nursing Care for Healthy Babies to Improve Sleep Quality and Smooth Defecation - Suparmi, Suparmi (Archives of The Medicine and Case Reports, 2024)
Baby massage is a form of physical touch that provides many benefits for babies, including improving sleep quality and smooth bowel movements. This study aims to determine the effect of baby massage on nursing care for healthy babies to improve sleep quality and smooth defecation in babies in Purwakarta Regency, Indonesia. This research is experimental research with a pre-test and post-test design. The research sample was 30 healthy babies aged 3-12 months who were grouped into two groups, namely the intervention group (15 babies) and the control group (15 babies). The intervention group was given baby massage for 10 minutes every day for 7 days. The control group was not given any treatment. Data on sleep quality and bowel movement were collected before and after the intervention. The results showed that there were significant differences between the intervention group and the control group in terms of sleep quality and smooth defecation. The intervention group showed greater improvements in sleep quality and smooth defecation compared to the control group. Based on the results of this research, it can be concluded that baby massage has a positive influence on improving sleep quality and smooth defecation in healthy babies.